A rare presentation of lung squamous cell carcinoma metastasis to the distal phalanx of the little finger: a case report. Issue 2 (1st August 2022) - Wu, Jianjun; Zhou, Yinan; Yang, Dawei; Yang, Fan
Abstract: Lung cancer is one of the most common malignant tumors worldwide. Early detection is the most important factor that affects the prognosis of lung cancer patients. The distal phalanx is a highly unusual metastatic site of lung cancer, and is often misdiagnosed, especially when accompanied by trauma. Herein, we present the case of a 68‐year‐old male patient who injured his right little finger. We hope this rare case will help clinicians to better diagnosis acral metastases of lung cancer to prolong patient survival. Abstract : Acrometastases of the hand are extremely rare and may be the first manifestation of lung cancer, but they consider a poor prognosis marker. It is important for physicians who encounter patients with a persistent lesion at the site of a wound located in the hand to earlier diagnosis. This recognition will improve patient care and may lead to earlier diagnosis of malignancy.